Major obstacles preventing governmental organizations in Abu Dhabi from implementing GIS - Almenhali, Amran Sulaiman (2012)
The last decade of the last century witnessed the emergence of the Geographic Information Systems technology (GIS) in the UAE and the Emirate of Abu Dhabi was one of the first beneficiaries of the promising technology. The Geographic Information Systems technology spread in Northern America and Europe, toppling the limited Technologies that used to offer very modest solutions that didn’t meet users’ increasing needs. The GIS technology addressed the problems that could not be solved by the old technologies and gave its users the peace of mind they were looking for. Despite of its effectiveness and rapid spread among the developed countries, the GIS technology spread among the governmental organizations in Abu Dhabi was not as rapid as expected. As the first decade of the twenty first century passed, there are still many governmental organizations in Abu Dhabi without GIS. This study looks at reasons behind the limited adoption of GIS and tries to identify as many reasons as possible, whether they are human related or non-human related. This study dedicates a major part of it to the GIS technology itself and its different components, because by knowing that will make it easy to find solutions to increase its adoption. Abu Dhabi government is considered to be one of the main beneficiaries of this study, because finding ways to spread this technology will enhance the performance of individual organizations, which in turn will be reflected in the government performance. The spatial dimension, which is the heart of the GIS technology, managed to attract major technology providers like Google and Apples, due to its importance. Therefore, governmental organizations in Abu Dhabi and the people in charge of them should use this technology to support the emirate’s goal to become one of the best governments in the world.